Development of an Electrochemical Biosensor Platform and a Suitable Low-Impedance Surface Modification Strategy - Pires Carneiro, Leonardo (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2014)
In this work, a flexible biosensor platform based on impedance spectroscopy and comprising of gold electrodes, polymeric flow cells and a suitable surface modification were developed. Initially, several surface modification techniques described in literature were implemented and optimized for impedimetric biosensors but their individual limitations rendered them unsuitable for this biosensor platform. A novel method based on photobleaching was developed and tested showing satisfactory results.